Vegetable consumption in Romania correlations with purchasing power and supply - Cornelia Alboiu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The paper makes an analysis of socio-economic factors that influence food consumption levels in terms of income evolution at regional level and also a comparison with EU average and several regions from Poland; it also presents the dispersion of regional GDP per inhabitant and its influence on consumption taking into account the level of polarization among several EU countries. The research analyses the level of expenditure per household in Romania; in addition comparisons with EU countries are made along with the structure of total average expenditure per person per month at macro region development levels in Romania. An in depth analysis is dedicated to the level of expenditures for vegetables and tinned vegetables and the structure of expenditure on the purchasing power for various types of vegetables by regions and social categories. The results show a quite high level of income dedicated for consumption and important disparities among social categories as far as the vegetable consumption is concerned. Also there is a high polarization among the EU countries concerning the income dispersion and its impact on vegetable consumption.
Keywords: 330; consumption; expenditure; purchasing power